Impaired Endothelial Dysfunction In Patients With Ankylosing Spondylitis After Covid-19 (Texas Journal of Medical Science, 2024)
Currently, there is no doubt about the importance of the role of impaired endothelial functional state in the development of vascular pathology in a number of diseases, including rheumatic. With the advent and largescale spread of a new coronavirus infection (COVID-19), a high rate of patient’s hospitalizations with ankylosing spondyloarthritis (AS) and the development of extrapulmonary complications, such as myocardial injuries, kidney damage and vascular thromboembolism, were noted. The development of this phenomenon confirms the connection with pronounced endothelial dysfunction and its damage. This article presents the results of evaluation of endothelial dysfunction in AS patients undergoing COVID-19.